Protective Effect of Cafestol on Doxorubicin-induced Genotoxicity in Rats - Sara A. Al-Kenany; N. Al-Shawi, Nada (Iraqi Journal of Pharmaceutical Sciences, 2023)
Doxorubicin is an efficient antineoplastic agent that has a broad antitumour spectrum; however, its genotoxic adverse effects on normal cells can be produced through oxidative damage, and this limits its clinical application. Cafestol is a naturally-occurring diterpene in unfiltered coffee with noteworthy antioxidant, antimutagenic and anti-inflammatory activities.The present study aimed to investigate the possible protective effect of cafestol against doxorubicin-induced chromosomal and DNA damage in rat bone marrow cells. WistarAlbino rats of both sexes were administered cafestol (5mg/kg body weight once daily for 14 consecutive days) by oral gavage alone or with doxorubicin which was injected as a single dose (90 mg/kg intraperitoneally at day 14) to induce toxicity. The bone marrow was harvested 24 hours after doxorubicin’s injection in all groups for the assessment of structural chromosomal aberration, micronucleus, and comet assays. The result showed that rats in the doxorubicin-only group exhibited a significant decrease (P<0.05) in mitotic index with a significant elevation (P<0.05) in the % DNA in Tail, micronucleus appearance and total structural chromosomal aberrations compared to those of the negative control group; while oral administration of cafestol 14 days prior to doxorubicin, significantly-reduced the % DNA in Tail, micronucleus appearance, and the total number of chromosomal aberrations (P<0.05), and improved the mitotic index compared to rats intraperitoneally-injected with doxorubicin alone. This study revealed that cafestol has protective effects against the genotoxicity induced by doxorubicin.